Infections of Larval Stages of Dicrocoelium dendriticum and Brachylaima sp. in Brown Garden Snail, Helix aspersa, in Turkey - Köse, Mustafa (Korean J Parasitol, 2015)
The aim of this study was to determine the presence and prevalence of larval stages of Dicrocoelium dendriticum and Brachylaima sp. in the first intermediate host, a species of land snail, Helix aspersa, in Turkey. A total of 211 snails were collected in April-May 2014 from pastures in Mersin District. Larval stages of D. dendriticum were identified under a light microscope. Hepatopancreas from naturally infected H. aspersa snails were examined histologically. The prevalence of larval stages of D. dendriticum and Brachylaima sp. in H. aspersa snails was found to be 2.4% and 1.9%, respectively, in Mersin, Turkey. Cercariae were not matured in sporocysts at the beginning of April; however, it was observed that cercariae matured and started to leave sporocysts by early-May. Thus, it was concluded that H. aspersa acts as an intermediate host to D. dendriticumin and Brachylaima sp. in Mersin, Turkey. A digenean trematode Brachylaima sp. was seen for the first time in Turkey.